De novo transcriptome assembly and developmental mode specific gene expression of Pygospio elegans. Issue 4 (4th September 2017) - Heikkinen, Liisa K.; Kesäniemi, Jenni E.; Knott, K. Emily
Abstract : Species with multiple different larval developmental modes are interesting models for the study of mechanisms underlying developmental mode transitions and life history evolution. Pygospio elegans, a small, tube‐dwelling polychaete worm commonly found in estuarine and marine habitats around the northern hemisphere, is one species with variable developmental modes. To provide new genomic resources for studying P. elegans and to address the differences in gene expression between individuals producing offspring with different larval developmental modes, we performed whole transcriptome Illumina RNA sequencing of adult worms from two populations and prepared a de novo assembly of the P. elegans transcriptome. The transcriptome comprises 66, 233 unigenes, of which 33, 807 contain predicted coding sequences, 26, 448 have at least one functional annotation, and 3, 076 are classified as putative long non‐coding RNAs. We found more than 8, 000 unigenes significantly differentially expressed between adult worms from populations producing either planktonic or benthic larvae. This comprehensive transcriptome resource for P. elegans adds to the available genomic data for annelids and can be used to uncover mechanisms allowing developmental variation in this and potentially other marine invertebrate species.